TRANSFER PRICING: CHALLENGES AND SOLUTIONS WITHIN THE ASEAN REGIME - Florence, Jane (Indonesian Journal of International Law, 2016)
Transfer pricing has recently gained a prominent highlight in ASEAN countries. Eventhough transfer pricing policy has already been enacted by most of each ASEAN member states, there still exists loopholes – especially involving the transactions of cross border transfer prices. This research paper will discuss and further scrutinize the legal issues constituted by these loopholes, which affect both member states and Multi National Enterprises (“MNEs”) - particularly those associated with deficit tax revenue suffered by the member states, as a result of transfer pricing manipulations conducted by the MNEs. Transfer pricing concealed in the form of crossborder transactions; including but not limited to acquisitions, joint venture, and supply chains - impedes the movement of trade and capital, even catalyzes a tax distortion. Aside from ASEAN member states, MNEs are also being put at a disadvantage – to be subjected to a much greater burden on paying a higher cost of compliance, due to its responsibility to comply with more than one country’s jurisdiction and to have them imposed towards a susceptible double taxation.The result of this study encourages and essentially demonstrates the necessity of ASEAN to leverage a firm legal framework on transfer pricing that emphasizes on the manifestation of ‘arm’s length principle’ in all ASEAN countries’ jurisdictions.